Popularization of Integrative and Complementary Healthy Practices (Research, Society and Development, 2022)
The Integrative and Complementary Practices in Health (PICS) represent a set of therapeutic systems that use technologies that aim at the prevention of diseases and the recovery of health. These practices contribute to reducing public spending and the use of services of the Sistema Único de Saúde. Given the relevance of PICS, this study aimed to characterize the perception and use of PICS by brazilians of Southern region. This is an observational, cross-sectional study carried out through the application of a questionnaire with semi-structured questions about the sociodemographic profile of individuals and aspects that cover the use of PICS in Southern Brazil. Descriptive frequency statistics were used to describe the results. The Chi-square test was also used to test possible associations between variables. The study had 213 participants, most of them female and between 18 and 25 years old. Most participants recognize the benefits of using PICS, however, they are not in the habit of using them. The relevance of disseminating PICS among the population is highlighted, as well as their benefits encouraging their use and health promotion.